Impact of Portfolio Assessment on Physics Students' Outcomes: Examination of Learning and Attitude - (:unkn) unknown (MODESTUM LTD, 2014)
In spite of the commendations for the use of portfolio assessment, there is still little evidence indicating that such assessment actually supports and encourages student learning. Hence, this research study aimed to empirically identify the effects of implementation of portfolio assessment on student learning and attitudes. True-experimental design was used for the study. Participants of the research were nine-grade students. Portfolio assessment was implemented in the experimental group for eight-week duration in the physics course. Findings illustrate that the students assessed by the portfolio constructed more knowledge than the students that did not prepare a portfolio. On the other hand, portfolio assessment did not make any difference in the students' attitudes towards physics. This study concludes that portfolios are not only an indication for student growth but also a learning tool.
Keywords: Portfolio assessment; learning; attitude; physics; FORMATIVE ASSESSMENT; TEACHERS; KNOWLEDGE; EDUCATION; DYNAMICS; OPTICS